The cost-effectiveness of 5-FU-SA in the treatment of actinic keratoses of the face and scalp in the UK secondary care setting. (4th March 2017) - Wojcik, Radek; Lowin, Julia; Vilardell, David; Maeso, Silvia; Ruiz, Leonardo; Lear, John T.; Morton, Colin
Abstract: Objective: The objective of this analysis was to estimate the relative cost-effectiveness of Actikerall 1 (5-FU-SA) vs cryotherapy in a secondary care setting in the UK, for lesion-directed treatment in patients with actinic keratoses (AK) of the face and scalp. Methods: The model was a simple decision tree, with a 6-month time horizon. The perspective was that of the UK National Health Service (NHS). Modeled treatment effects included reported per-patient histological clearance and recurrence rates. Cost inputs comprised professional consultation time and cost of medication. Health-related utility estimation followed previously published methodology. Adverse events were not modeled. The key data and model structural assumptions followed expected UK practice. One-way and probabilistic sensitivity analyses were conducted to assess structural and parameter uncertainty. Results: 5-FU-SA was found to be less costly (−£204) and more effective (+0.001 QALY) in base case and sensitivity analyses. In the probabilistic analysis there was 100% probability of being cost-effective over cryotherapy at £20, 000 willingness to pay. Cost of professional time was a key driver of the model outcome. 5-FU-SA remained dominant across a range of scenario analyses, including exploration of assumptions around setting of care. Limitations: The time horizon of the analysis was short and data were not extrapolated beyond the duration of the clinical trial; however, this approach is consistent with likely follow-up of an AK patient. The clinical outcomes observed in the trial were based on a large proportion of cryotherapy patients undergoing an additional cycle of treatment; this may not occur or be required in an experienced secondary care setting. Conclusion: 5-FU-SA could be considered as a cost-effective choice for treatment of AK lesions of the face and scalp in secondary and mixed care settings in the UK. Use of 5-FU-SA in patients who would otherwise be managed with cryotherapy has the potential to result in cost savings.